Phase- and morphology-controlled synthesis of tunable plasmonic MoO3-x nanomaterials for ultrasensitive surface-enhanced raman spectroscopy detection - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Mukherjee, Shatabdi Porel (Journal of Physical Chemistry C, 2020)
The enhancement of the surface-enhanced Raman scattering (SERS) property of the plasmonic metal oxide semiconductor nanostructures by controlling their phase, shape, size, and oxygen vacancy to detect trace amounts of organics is of significant interest. In this study, a simple surfactant-free hydrothermal strategy was proposed to fabricate crystalline h-MoO3-x and alpha-MoO3-x nanomaterials with tunable plasmonic properties. Herein, the crystal phase, morphology, and oxygen vacancy of MoO3-x nanostructures were precisely controlled under suitable synthetic conditions. The plasmonic properties of the as-synthesized h-MoO3-x and alpha-MoO3-x micro-/nanostructures were controlled by adjusting the residual volume in the autoclaving chamber. In addition, the plasmonic MoO3-x exhibited SERS activity with a detection limit as low as 1.0 x 10(-9) M and the maximum enhancement factor (EF) up to 6.99 x 10(5) for h-MoO3-x, while for alpha-MoO3-x, the detection limit was 1.0 x 10(-7) M with the corresponding EF up to 8.51 x 10(3), comparable with plasmonic noble metal nanomaterials without a ``hot spot''.